Effect of Psidium guajava L on Biofi lm Forming Multidrug Resistant Extended Spectrum Beta Lactamase (ESBL) Producing Pseudomonas aeruginosa (Tribhuvan University Journal of Microbiology, 2019)
Objectives: In order to investigate the relative efficacy of Psidium guajava L (guava) leave, in vitro antibacterial effect of ethanolic extract and leaf tea of guava against pathogenic Pseudomonas aeruginosa was carried out.Methods: This study was carried out at Microbiology laboratory of KIST medical college and teaching hospital, Lalitpur. Pseudomonas aeruginosa was isolated from different clinical samples. Antibiotic susceptibility of the isolates was performed by Kirby-Bauer disk diffusion method. Biofilm formation was detected by microtitre culture plate method and ESBL production by combine disk methods. Antimicrobial activity of guava leaf tea and ethanol extract of leaf were determined by agar well diffusion method.Results: Ethanol extract of fresh guava leaves exhibited higher antibacterial activity than dry and fresh leaves tea, but significantly less than the standard antibiotics. In this study, 7% of the total bacterial isolates were P. aeruginosa with 65.30% of these isolates being MDR. Similary, significant number of these MDR strains ie. 83.67% of these P. aeruginosa isolates produced biofilm. While as 6.12% of the isolated were ESBL producer.Conclusion: The leaves extract of guava have shown effective result against P. aeruginosa and could serve as good source of antibacterial agents. Guava leaves extract can be an economic alternative to antibiotics. However, active compound of this extract need to be purified and pharmacologically tested before its application.